Respostas

2014-05-13T21:26:49-03:00
A) 5.(8-4)=

5.(8-4) =
5.(4) = 20

b) 2.5:(-5)+(-30)=
2.5 : (-5) + (-30) =
 10 :(-5)  - 30 =
     - 2      - 30  = - 32

c) 2³.3-9=
2³ . 3 - 9 =
8 . 3 - 9 =
 24   - 9 =  15


d) 15°-raiz de 16- 2³=

 15º - √16 - 2³ =
   1   -  4   - 8  = - 13


e) 19-(-20):(-2)=

19 -(-20) : (-2) =

19 + 20 : (-2) =

19   -   10 =  9


f) 15:(-5)+2.(-4)³=

15 : (-5) + 2.(-4)³ =
    -3      + 2(-64) =
   - 3    -  128 =  - 131




g) 61-4.(-15)+202:(-2)=

61 - 4 . (-15) + 202 : (-2) =
61 +     60     -     101      =
121 - 101 =  20
1 5 1